Gut Microbiota Dysbiosis in the Pathogenesis of Metabolic-dysfunction Associated Steatotic Liver Disease (MASLD) - Mir, Gh Jeelani; Ashraf, Nissar Ul (The International Journal of Gastroenterology and Hepatology Diseases, 2024)
Metabolic-dysfunction-associated steatotic liver disease (MASLD), previously referred to as nonalcoholic fatty liver disease (NAFLD), affecting approximately 30% of the global population. Projections suggest that MASLD incidence may rise by up to 56% over the next decade. MASLD has become the fastest-growing cause of hepatocellular carcinoma (HCC) in the USA, France, UK, and other regions worldwide. The prevalence of MASLD and MASLD-related liver damage is expected to parallel the increasing rates of obesity and type 2 Diabetes Mellitus (T2DM) globally. The factors contributing to MASLD development and its progression to metabolic-dysfunction-associated steatohepatitis (MASH), fibrosis, cirrhosis, and HCC remain poorly understood. Evidence from cell-based, animal-based, and human-subject studies suggests that insulin resistance, endoplasmic reticulum stress, oxidative stress, impaired autophagy, genetics, epigenetics, reduced immune surveillance, increased gut inflammation, and gut dysbiosis are crucial events in MASLD pathogenesis. In recent years, dysregulation of gut microbiota has emerged as a potential mechanism implicated in MASLD and MASLD-related hepatocarcinogenesis. This review briefly outlines the mechanistic events significant for MASLD pathogenesis. Additionally, it offers insight into dysregulated gut microbiota and its correlation with MASLD and MASLD-related liver damage. Furthermore, it highlights pertinent questions for cell and microbiologists in the MASLD research field. It underscores the necessity for identifying factors leading to gut microbiome dysregulation in MASLD and MASH pathogenesis. Identifying these factors could aid in the development of novel strategies for managing MASLD and MASLD-related liver damage.
Keywords: MASH/NASH